Vocational High School Students' Marketing Strategies in Socio-Economic Development Using Digital Technology in the 21st Century Era - Anshar Daud (Universitas Pendidikan Ganesha, 2025)
The limited implementation of digital marketing strategies by Vocational High School (SMK) students in promoting their businesses and products has become a significant issue in the digital economy era. Although most students have access to the internet, the utilization of social media and digital platforms for marketing activities remains suboptimal. This study aims to analyze and evaluate the factors influencing the effectiveness of students’ digital marketing strategies and to explore the various challenges they encounter in their implementation. The research employed a mixed-methods approach involving 480 vocational high school students selected through random sampling. Data were collected through online questionnaires, observations, interviews, and document analysis. Quantitative data were analyzed descriptively using SPSS version 29.0, while qualitative data were examined through data reduction, coding, categorization, and conclusion drawing. The findings reveal that students’ limited digital marketing literacy and skills, along with inadequate supporting infrastructure, constitute the primary obstacles to effective marketing strategies. The study concludes that strengthening systematic digital marketing education and training is essential. The implications highlight the importance of integrating a more market-responsive curriculum and enhancing practice-based learning to sustainably develop students’ digital marketing competencies.